Development of Photo Electrocatalytic Chemical Oxygen Demand Design (PECOD) Sensor using Highly Ordered Titanium Dioxide Nanotube Arrays Electrodes - Utami, Chichi Amne; Syauqi, Muhammad Iqbal; Ningsih, Sherly Kasuma Warda; Wibowo, Rahmat; Gunlazuardi, Jarnuzi (Chimica et Natura Acta, 2024)
Population growth, industrialization, and the need to ensure water quality have fostered the demand for analytical methods and tools to determine one of the important values of water quality standards. The oxygen demand of a given water matrix provides valuable information about the presence of organic compounds in a sample. The TiO2-based photoelectrocatalytic COD (PECOD) method offers a faster, more efficient, and more accurate alternative than conventional methods. Highly ordered TiO2 nanotube arrays (HOTNAs) were synthesized by anodizing titanium metal at 45V for 2 hours. HOTNAs/FTO photoanodes are used to oxidize organic compounds in water. HOTNAs/FTO photoanode has a bandgap of 3.4eV and a current density of 0.29 mA/cm2. Environmental samples were tested with the PeCOD sensor using glucose and mixed compound addition standards method. Water samples taken from local small ponds, namely Danau Kenanga, Danau Agathis, and typical wastewater of Laundry activity reveal COD values of 15,4659 to 15,9571 mg/L O2; 19,0500 to 19,6179 mg/LO2; 445,2336 to 449,7830 mg/L O2; respectively. The developed PECOD sensor performed well and provided analytical results that were not much different from conventional methods, with an error percentage below 10%.